An evaluation of activation and radiation damage effects for the European Spallation Source Target. Issue 5 (4th May 2018) - Mora, Tomás; Sordo, Fernando; Aguilar, Adrian; Mena, Luis; Mancisidor, Maite; Aguilar, Jorge; Bakedano, Gorka; Herranz, Iñigo; Luna, Paula; Magan, Miguel; Gonzalez-del Moral, Octavio; Vivanco, Raul; et al.
ABSTRACT: The details concerning the generation and accumulation of radionuclides produced by spallation reactions within the neutron generation target to be installed at the European Spallation Source are described. The resulting radiation damage for the target tungsten blocks constituents as well as the target encasing is evaluated and explicit results are given for the effects of knock-on atoms as well as those resulting from the accumulation of light and volatile hydrogen and helium isotopes resulting from spallation reactions. Their effects on the mechanical properties are discussed on the light of available experimental data and, on this basis, an estimation of the target lifetime is given.